2020
DOI: 10.1002/admt.202000147
|View full text |Cite
|
Sign up to set email alerts
|

Photothermally Reconfigurable Shape Memory Magnetic Cilia

Abstract: Stimulus-responsive polymers are attractive for microactuators because they can be easily miniaturized and remotely actuated, enabling untethered operation. In this work, magnetic Fe microparticles are dispersed in a thermoplastic polyurethane shape memory polymer matrix and formed into artificial, magnetic cilia by solvent casting within the vertical magnetic field in the gap between two permanent magnets. Interactions of the magnetic moments of the microparticles, aligned by the applied magnetic field, drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Similarly, another artificial cilia array was reported [ 118 ], fabricated using the PDMS and CrO 2 nanoparticles. The study has discussed the multi-responsive technique [ 119 ], where apart from actuating artificial cilia through the magnetic field, the shape can be further reconfigured through photo-thermal heating.…”
Section: Artificial Cilia Actuation Methodologiesmentioning
confidence: 99%
“…Similarly, another artificial cilia array was reported [ 118 ], fabricated using the PDMS and CrO 2 nanoparticles. The study has discussed the multi-responsive technique [ 119 ], where apart from actuating artificial cilia through the magnetic field, the shape can be further reconfigured through photo-thermal heating.…”
Section: Artificial Cilia Actuation Methodologiesmentioning
confidence: 99%
“…Recently, Liu et al. [ 29 ] reported that the micropillar can be easily obtained by the self‐assembly method, but the structure is hard to keep consistent. To the best of our knowledge, the noncontact, all‐in‐situ reversible configuration of magnetic particles doped SMP microscale structures to achieve the manipulation of liquid droplets with microscale size has rarely been reported (Figure S1, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…These can be deformed and molded into a temporary shape, and then recovered at different temperatures, lighting conditions, and salt concentrations in solution. [ 16–26 ] The heat‐triggered SMP possesses a shape memory effect similar to that of SMA. It can be programmed into a temporary shape when the temperature is higher than the melting point of the temperature‐controlling component, then fixed through cooling, and finally reverted to its original shape through reheating.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the good mechanical properties of non‐magnetic matrices and the unique magneto‐induced capability of ferromagnetic particles, magnetorheological elastomers (MREs) have promising applications, such as untethered actuation, [ 26,44–49 ] vibration control, [ 50–53 ] and non‐contact sensing. [ 31,36,54–58 ] Under an external magnetic field, the magnetic interactions of the particles actuate the matrix, and the gaps between the conductive fillers and magnetic particles are varied, resulting in changing conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation